Misbehavior in Organizations: A Motivational Framework - Vardi, Yoav; Wiener, Yoash (Organization Science, 1996)
Observers of organizations recognize now that work related misconduct is both pervasive and costly. There is ample evidence that members of organizations sabotage processes, steal company property, harass others, cheat the government, or mislead customers. Companies and the public pay dearly. What are the motivational forces that drive organizational members to exhibit such varied forms of misconduct? Are these forces different from those that drive them to engage in constructive behavior? What kinds of personal and organizational factors influence such acts of intentional misbehavior? Our basic objectives in this paper are three-fold; first, to formally define a new construct of Organizational Misbehavior (OMB), and to discuss the theoretical implications of the definition; second, to identify different types of OMB; and third, to develop a conceptual framework that would allow the inclusion of OMB in a comprehensive theory of work motivation, applicable to both proper and improper conduct. We define Organizational Misbehavior as “any intentional action by members of organizations that violates core organizational and/or societal norms.” A crucial element in the definition is the intention underlying the misbehavior. It therefore serves as the basis for the distinction among three types or organizational misbehavior: (a) OMB Type S, misbehavior that intends to benefit the self; (b) OMB Type O, misbehavior that intends to benefit the organization; and (c) OMB Type D, misbehavior that intends to inflict damage. In order to integrate these forms of misconduct within a comprehensive motivational framework, we use the distinction between normative and instrumental sources of motivation. We propose that people who engage in OMB Type S are primarily motivated by self-interest consideration (i.e., instrumental processes), whereas those that perpetrate OMB Type O do so mostly because of strong identification with and loyalty to their organization (i.e., normative processes). OMB Type D, however, may he triggered by either instrumental or normative forces, or by both at the same time. The various instrumental and normative factors that influence misbehavior are not only personal; they can also be organizational. On the individual level, we refer to such factors as the stage of moral development and personal need satisfaction At the organization level, we examine the role of such factors as organization culture and cohesiveness. We finally use the instrumental-normative framework to derive a set of formal propositions about the effects of some of these factors on the form and intensity of OMB.